The North Tambey uplift history study using 3D seismic data - Yu. A. Zagorovsky (Georesursy, 2024)
Paper shows the information about the geological and geophysical exploration of Tambeyskoye natural gas field located in the north of the Yamal Peninsula. The problems with mapping of natural gas deposits in Cretaceous and Jurassic formations are described. The results of formation thickness analysis are presented in order to explain the reasons for the unprecedented concentration of separate natural gas accumulations and the heterogeneous saturation of massive reservoirs in Cretaceous formations. The method of paleotectonic analysis is briefly described, the initial data are reported. Structural and isopach maps are presented. Structural elements and their evolution in Jurassic and Cretaceous time are presented. It was concluded that different structural elements of the work area transformed quite independently until the end of Cenomanian. The modern shape of North Tambey uplift was forming during the Neogene to Quarter age. Natural gas bearing reservoirs in Jurassic formation with the overpressure were reported. The young age of the North Tambey uplift, the unprecedented concentration of separate natural gas accumulations, the and the heterogeneous saturation of massive reservoirs in Cretaceous formations, overpressure in Jurassic formation – all these facts show that the Tambeyskoye natural gas field is under active gas accumulation. Hydrocarbon gases coming from deep Jurassic formations and it was not enough time for gas accumulations to be distributed over the reservoirs of Cretaceous.